Optimization and Characterization of Liquid Fuels Obtained from the Pyrolysis of High Density Polyethylene Waste (LACCEI, 2024)
A multiple regression analysis was performed to automatically fit a model for optimizing the performance of liquid fuels obtained from the pyrolysis of high-density polyethylene (HDPE). The test version of the "Minitab 17" software was used, being the objective value, the yield of liquid products, and as variables, the pyrolysis operation temperature and the particle size of the sample. From the model, it was found that the operating conditions that maximize the performance of liquid fuels are a pyrolysis operating temperature of 557.8 °C and a particle size of 3 cm. It was possible to determine that the liquid products obtained contained fractions of 18% gasoline cut, 32% Naphtha/Kerosene, 28% diesel cut, and 22% residual. Likewise, a chemical composition analysis was carried out in which it was determined that the liquid products contained hydrocarbons, aromatics, halogenated, sulfur, and oxygenated components.